Do You See What I See: Recognition of Protozoan Parasites by Toll-Like Receptors - Ghosh, Debopam; S. Stumhofer, Jason (Current Immunology Reviews (Discontinued), 2013)
Toll-like receptors (TLRs) are important for recognizing a variety of pathogens, including protozoan parasites, and initiating innate immune responses against them. TLRs are localized on the cell surface as well as in the endosome, and are implicated in innate sensing of these parasites. In this review, we will discuss recent findings on the identification of parasite-derived pathogen associated molecular patterns and the TLRs that bind them. The role of these TLRs in initiating the immune response against protozoan parasitic infections in vivo will be presented in the context of murine models of infection utilizing TLR-deficient mice. Additionally, we will explore evidence that TLRs and genetic variants of TLRs may impact the outcome of these parasitic infections in humans.
Keywords: innate immune response